Availability and Use of Cheap Tobacco in the United Kingdom 2002–2014: Findings From the International Tobacco Control Project - Partos, Timea R (Nicotine Tob Res, 2018)
INTRODUCTION: Raising tobacco prices is the most effective population-level intervention for reducing smoking, but this is undermined by the availability of cheap tobacco. This study monitors trends in cheap tobacco use among adult smokers in the United Kingdom between 2002 and 2014 via changes in product type, purchase source, and prices paid. METHODS: Weighted data from 10 waves of the International Tobacco Control policy evaluation study were used. This is a longitudinal cohort study of adult smokers with replenishment; 6169 participants provided 15812 responses. Analyses contrasted (1) product type: roll-your-own (RYO) tobacco, factory-made packs (FM-P), and factory-made cartons (FM-C); (2) purchase source: UK store-based sources (e.g., supermarkets and convenience stores) with non-UK/nonstore sources representing tax avoidance/evasion (e.g., outside the UK, duty free, and informal sellers); and (3) prices paid (inflation-adjusted to 2014 values). Generalized estimating equations tested linear changes over time. RESULTS: (1) RYO use increased significantly over time as FM decreased. (2) UK store-based sources constituted approximately 80% of purchases over time, with no significant increases in tax avoidance/evasion. (3) Median RYO prices were less than half that of FM, with FM-C cheaper than FM-P. Non-UK/nonstore sources were cheapest. Price increases of all three product types from UK store-based sources from 2002 to 2014 were statistically significant but not substantial. Wide (and increasing for FM-P) price ranges meant each product type could be purchased in 2014 at prices below their 2002 medians from UK store-based sources. CONCLUSIONS: Options exist driving UK smokers to minimize their tobacco expenditure; smokers do so largely by purchasing cheap tobacco products from UK stores. IMPLICATIONS: The effectiveness of price increases as a deterrent to smoking is being undermined by the availability of cheap tobacco such as roll-your-own tobacco and cartons of packs of factory-made cigarettes. Wide price ranges allowed smokers in 2014 to easily obtain cigarettes at prices comparable to 12 years prior, without resorting to tax avoidance or evasion. UK store-based sources accounted for 80% or more of all tobacco purchases between 2002 and 2014, suggesting little change in tax avoidance or evasion over time. There was a widening price range between the cheapest and most expensive factory-made cigarettes.